Development of Science Learning Media Based on Augmented Reality Book with Problem Based Learning Model to Improve Learning Outcomes of Third Grade Students - Sapira; Isa Ansori (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted based on the findings of problems in the field, one of which is the learning outcomes of students in science learning are still low compared to other learning. The purpose of this study was to determine the development, feasibility, and effectiveness of Augmented Reality Book learning media as a science learning media on water cycle material in elementary schools. The method used is R & D (Research & Development), and the development model used is the ADDIE model. The results of research and development are obtained from the results of feasibility trials and the results of usage trials. From media experts get a percentage of 91.67% with a very feasible category and from material experts get a percentage of 90.38% with a very feasible category. The results of the small group usage trial obtained an average posttest of 81.30 with an average pretest value of 54. While the results of the large group usage trial obtained an average posttest of 79.18 with an average pretest value of 50.27. With an increase in learning outcomes in the moderate category of 61% in small groups, while in large groups there was an increase in learning outcomes in the moderate category of 58%. So it can be concluded that AR-Book-based science learning media on water cycle material effectively improves student learning outcomes. For this reason, researchers hope that there is support for more complete learning facilities so that the application of using the media is more effective and more efficient.